2002
DOI: 10.1155/np.2002.233
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Median Raphe Nucleus to ContextualFear Conditioning and Fear‐Potentiated Startle

Abstract: Ascending 5-HT projections from the median raphe nucleus (MRN), probably to the hippocampus, are implicated in the acquisition of contextual fear (background stimuli), as assessed by freezing behavior. Foreground cues like light, used as a conditioned stimulus (CS) in classical fear conditioning, also cause freezing through thalamic transmission to the amygdala. As the MRN projects to the hippocampus and amygdala, the role of this raphe nucleus in fear conditioning to explicit cues remains to be explained. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
2
23
0
7
Order By: Relevance
“…Considering the similarity of synaptic changes, these results strongly suggest that 5-HTergic function in the MRN-hippocampus pathway is involved in gender differences in response to fear stress. These findings were supported by the results observed in lesion studies in the males; freezing expression during exposure to CFC was reduced by electrical lesion of the MRN, as reported in the males with neurotoxic lesions of the MRN (47). Reduction of freezing in the MRN-lesioned males is similar to the CFC-induced behavioral pattern in the females.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the similarity of synaptic changes, these results strongly suggest that 5-HTergic function in the MRN-hippocampus pathway is involved in gender differences in response to fear stress. These findings were supported by the results observed in lesion studies in the males; freezing expression during exposure to CFC was reduced by electrical lesion of the MRN, as reported in the males with neurotoxic lesions of the MRN (47). Reduction of freezing in the MRN-lesioned males is similar to the CFC-induced behavioral pattern in the females.…”
Section: Discussionsupporting
confidence: 86%
“…There is further topographical organization within the DRN itself. Although the possible significance of this organization will not be discussed here, Lowry and colleagues among others have shown that certain DRN subregions appear to be preferentially involved in stress and anxiety (Abrams et al, 2004(Abrams et al, , 2005Lowry, 2002;Maier and Watkins, 2005;Silva et al, 2002).…”
Section: Serotonin Releasementioning
confidence: 99%
“…A amígdala, o hipocampo e o núcleo mediano da rafe estão criticamente envolvidos na regulação das respostas de medo condicionado contextual (MCNISH, 1997;AVANZI;BRANDÃO, 2003;BRANDÃO, 2004).…”
Section: Substrato Neuralunclassified
“…Desta forma, as projeções serotoninérgicas que saem do NMR, principal fonte de transmissão serotoninérgica no encéfalo, em direção à amígdala e ao septo-hipocampo são de grande importância na modulação do medo contextual (AZMITIA; SEGAL, 1978;GRAY;MCNAUGHTON, 2000;SILVA et al, 2002).…”
Section: Substrato Neuralunclassified
See 1 more Smart Citation